2004
DOI: 10.1515/comm.2004.012
|View full text |Cite
|
Sign up to set email alerts
|

Viewing behavior of children and TV guidance by parents: A comparison of parent and child reports.

Abstract: In this study parents as well as their children (N ϭ 224) were surveyed about children's television viewing behavior and television guidance provided by parents. It was investigated whether parents know how much time their child spends in front of the television and which programs the child watches. Parents' estimate of their children's viewing time was consistently lower than the estimate made by the children themselves. Parents showed to know about half of the programs the child reported to watch at home. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
(46 reference statements)
1
20
0
2
Order By: Relevance
“…Previous television and video game research has shown that children and their parents usually agree on the types of mediation they identify but differ in the amount of mediation they perceive; parents usually report more involvement than their children (Koolstra & Lucassen, 2004;Nikken & Jansz, 2006;van der Voort, van Lil, & Peeters, 1998). Several explanations are conceivable here.…”
Section: Dissimilarity Between Parents and Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous television and video game research has shown that children and their parents usually agree on the types of mediation they identify but differ in the amount of mediation they perceive; parents usually report more involvement than their children (Koolstra & Lucassen, 2004;Nikken & Jansz, 2006;van der Voort, van Lil, & Peeters, 1998). Several explanations are conceivable here.…”
Section: Dissimilarity Between Parents and Childrenmentioning
confidence: 99%
“…First, parents may exaggerate their interventions in order to comply with norms of socially desirable behaviour, whilst children may minimize parental mediation for reasons of peer status (van der Voort et al, 1998). This explanation is not sufficient, however, because the differences between parents and children can vary significantly per type of mediation (Koolstra & Lucassen, 2004). Second, the difference may be due to the characteristics of children's media use and modern family life.…”
Section: Dissimilarity Between Parents and Childrenmentioning
confidence: 99%
“…This follows also from research that indicates that the way in which parents interfere with their children's media use depends on the family background (Warren, Gerke, and Kelly, 2002). Parental interference is often studied under the labels of 'parental guidance' or 'parental mediation' (for a discussion of this concept, see Koolstra and Lucassen, 2004). These labels suggest that parental interference with media use by their (adolescent) children is deliberately induced with children's well-being in mind.…”
Section: Media Use Of Adolescents and Their Parentsmentioning
confidence: 99%
“…Previous research on television has shown that parents and children perceive differently the amount of parental mediation which takes place, and usually parents report that they are more involved than is recognised by their children (Van Den Bergh and Van Den Bulck, 2000;Koolstra and Lucassen, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, parents may overestimate their behaviour in order to comply with the norms of "socially desirable behaviour", whereas children may minimize parental mediation for reasons related to peer status (Van Den Bergh and Van Den Bulck, 2000;Van Der Voort, Van Lil, and Peeters, 1998). Nevertheless, this explanation is insufficient as differences between children's and parents' versions of the degree of parental mediation carried out can vary significantly, depending on the type of mediation involved (Koolstra and Lucassen, 2004). Secondly, handheld devices increasingly allow children to use them out of the sight of their parents, either in their bedroom or with peers.…”
Section: Introductionmentioning
confidence: 99%